2017
DOI: 10.1111/pbr.12456
|View full text |Cite
|
Sign up to set email alerts
|

Correlated effects of exotic pollen‐fertility restorer genes on agronomic and quality traits of hybrid rye

Abstract: In CMS (cytoplasmic male sterility)‐based hybrid rye (Secale cereale L.) breeding, effective pollen‐fertility restoration is an essential prerequisite for achieving maximum grain yield on the one hand and for minimizing ergot (Claviceps purpurea) infestation on the other. Restorer genes for the CMS‐inducing ‘Pampa’ cytoplasm derived from landraces collected in Iran and Argentina are used by breeders for achieving this goal. Here, restorer genes from four germplasm sources (‘Altevogt 14160’, ‘IRAN III’, ‘Trenel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…Klotz (2002) already showed that, similar to our results, an introgression of already 25% of the IRAN IX gene reduced ergot severity by 70%. It should be noted, however, that hybrids with a maximum percentage of a non-adapted restorer gene suffer from a significant grain yield reduction in earlier backcross stages (Miedaner et al 2017). The variance components of genotype, inoculum, environment and their interactions were all significant, the environment was the most important factor for all traits.…”
Section: Ri (%)mentioning
confidence: 92%
See 1 more Smart Citation
“…Klotz (2002) already showed that, similar to our results, an introgression of already 25% of the IRAN IX gene reduced ergot severity by 70%. It should be noted, however, that hybrids with a maximum percentage of a non-adapted restorer gene suffer from a significant grain yield reduction in earlier backcross stages (Miedaner et al 2017). The variance components of genotype, inoculum, environment and their interactions were all significant, the environment was the most important factor for all traits.…”
Section: Ri (%)mentioning
confidence: 92%
“…While the European restorer sources for the P cytoplasm are only partial restorers and prone to environmental changes and the seed parents, non-adapted, monogenically inherited restorer genes from Iranian primitive rye and Argentinean landraces provide nearly full restoration (Miedaner et al 2005). The latter showed, however, a considerable yield penalty even in higher backcross generations (BC 4 to BC 5 , Miedaner et al 2017). Additionally, the amount of pollen available from hybrid cultivars depends on the ease of restoration and/or physiological resistance mechanisms of the female parent.…”
Section: Introductionmentioning
confidence: 99%
“…The marker-assisted selection (MAS) breeding process was streamlined by the development of sequencecharacterized amplified region (SCAR) markers based on RAPD and AFLP markers tightly linked to the critical QTLs (Stracke et al 2003). However, long intervals between the markers flanking the Rfp1 (2.9 cm) and Rfp2 (5.2 cm) QTLs are problematic because the region may encode undesirable genes surrounding the introgressed allele (Frisch and Melchinger, 2000;Miedaner et al 2017). Recent development of accurate conserved ortholog set (COS) markers (TC300731 and TC256739) delimiting Rfp1 within a 0.7 cm interval (Hackauf et al 2012) and an EST-derived CAPS marker, c28385, which co-segregates with Rfp3 (Hackauf et al 2017), was also beneficial.…”
Section: Introductionmentioning
confidence: 99%
“…A high linkage drag of undesirable genes with the 4R QTL was observed in hybrids (Miedaner et al 2000(Miedaner et al , 2017. Two markers, namely Xtc256739 and Xtc300731, flanking the Rfp1 gene at distances of 0.3 cM and 0.4 cM were evaluated (Hackauf et al 2012).…”
Section: Introductionmentioning
confidence: 99%